miR-21 Regulates Immune Balance Mediated by Th17/Treg in Peripheral Blood of Septic Rats during the Early Phase through Apoptosis Pathway - Cheng Liu; Qi Zou (Biochemistry Research International)
Objective. To study the mechanism by which miR-21 regulates the differentiation and function of Th17/Treg cells in sepsis. Methods. A rat model with sepsis was made by cecal ligation and puncture (CLP). Then, some of the septic rats were transfected with miR-21 mimic or inhibitor by liposome. At 48 hours, lymphocytes and plasma from septic rats were isolated for further experimental detection. The expression of miR-21 in lymphocytes was detected by Polymerase Chain Reaction (PCR); the differentiation of Th17/Treg cells was counted by flow cytometry; lymphocyte apoptosis was observed by terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) assay. The caspase-3/9 proteins were tested by Western blot; IL-10 and IL-17 were detected by enzyme-linked immunosorbent assay (ELISA). Results. Compared with the sepsis group (SP group), the Th17 cells increased significantly, the Treg cells decreased significantly, the apoptosis rate of lymphocytes decreased significantly, the mRNA and proteins of caspase-3/9 decreased significantly, the IL-17 decreased, and the IL-10 increased in the sepsis group transfected with miR-21 (SP + miR-21 mimic group). After transfection of miR-21 inhibitor, the results were almost opposite to those of SP + miR-21 mimic group. Conclusions. The differentiation and function of Th17/Treg cells were regulated by miR-21 in sepsis through caspase pathway.